DIVERSIFIKASI PENGOLAHAN HASIL LAUT DALAM UPAYA PENCEGAHAN STUNTING DI DESA BABUL MAKMUR KABUPATEN SIMEULUE - Melki Alimon; Burhanis Burhanis; Radhi Fadhillah (Universitas Teuku Umar, 2022)
Simeulue Regency is ranked as the second highest stunting rate among other districts in Aceh Province. One of the villages showing the highest stunting rate is Babul Makmur in West Simeulue District. Therefore, it is necessary to conduct research on the diversification of marine product processing as an effort to prevent stunting in Babul Makmur Village. The research was conducted in Babul Makmur Village from November to December 2021. This study used qualitative methods, namely observation and interviews with 50 respondents. Based on the results, it was found that 78% of respondents had heard of functional food and some processed products from marine products. Then, 32% had known that fishery products are rich in protein, omega 3 and omega 6. The final evaluation showed that 74% of respondents had fully understood that consuming fish and shellfish could prevent malnutrition in children and toddlers. The results obtained indicate that the community had a good understanding of the use of seafood and the diversification of its processed products as an effort to prevent and control stunting in children and toddlers.Keywords: Diversification, Marine Products, Simeulue Regency, Stunting